In-situ simulation. (October 2018) - Schofield, Louise; Welfare, Emma; Mercer, Simon
'In-situ' simulation or simulation 'in the original place' is gaining popularity as an educational modality. This article discusses the advantages and disadvantages of performing simulation in the clinical workplace drawing on the authors' experience, particularly for trauma teams and medical emergency teams. 'In-situ' simulation is a valuable tool for testing new guidelines and assessing for latent errors in the workplace.